CORPORATE SOCIAL RESPONSIBILITY DALAM BINGKAI SYARIAH - Arditi Annisa H; Nuraini Nuraini (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
Research in corporate social responsibility (CSR) has long been established yet there are still new dimensions for its discussion within the Islamic perspective. This study undertakes the investigation of CSR within the Islamic banking industry utilizing the Shariah Enterprise Theory (SET). It seeks to identify whether the factors of size, profitability and shariah compliance may play role in the disclosure of CSR by Islamic banks in Indonesia. All registered Islamic banks in Indonesia publishing their annual report for the period of 2011-2016 were employed as samples of this study. The findings demonstrated that some of the sampled banks have provided extensive and informative disclosure of CSR. Simulteanously the three studied variables consisting of size, profitability and shariah compliance were found to influence the CSR disclosure. Nevertheless, partially while bank size and profitability were found to influence the CSR disclosure yet there was no influence of shariah compliance towards CSR disclosure. This gives an interesting insight for further examination in future studies